Thermal Analysis Of Carbon Fibre Reinforced Polymer Decomposition - Mohamad Yatim, Norazlina; Shamsudin, Zurina; Shaaban, Azizah; Abdullah Sani, Nurhernida; Jumaidin, Ridhwan; Shariff, Emy Aqila (Institute of Physics Publishing, 2020)
The increasing number of carbon fibers reinforced polymer (CFRP) waste disposed of in landfills is creating environmental concerns due to the potential release of toxic by-products and the need for recycling. This research work investigates the influence of atmosphere (single and combination of nitrogen and oxygen) and heating rate (5 and 10 °C min-1) on the thermal decomposition of CFRP to recover the reclaimed-cf The samples were heated up to 420 °C in a nitrogen atmosphere followed by heating in the oxygen atmosphere from 420 °C until the final heating temperature at different heating rates. The thermal decomposition behavior of the CFRP waste was compared by thermogravimetric analysis (TGA). Morphological, chemical and structural analysis of reclaimed-CF was performed using SEM, FT-IR and Raman spectroscopy respectively. A nitrogen atmosphere was significance at the early temperature (<420 °C) to decompose smaller molecules of epoxy resin components, while oxygen atmosphere is needed to achieve a complete separation of reclaimed-CF from their matrix. Thermal decomposition at lower heating rate (5 °C min-1) was found efficiently to eliminate the complex epoxy resin and retain the structure of reclaimed-cf The particular thermal decomposition technique that leads to a lower final heating temperature (540 °C) is present to recover valuable reclaimed-CF from complex CFRP industrial waste.